Karstwasserfläche und unterirdische Karstniveaus - Bögli, Alfred (ERDKUNDE, 1966)
The existence of karst water bodies and subterranean karst levels has by now been proved beyond a doubt. A karst water surface, like the level of water under pressure, behaves according to hydro-mechanical laws and is thus more aptly called a piezometric surface. Its location is largely determined by the main drainage. Together with the phreatic marginal zone this level is the place of intensive cave formation, in particular through a special kind of corrosion (Mischungskorrosion), which gives rise to extensive subterranean gallery systems, the so-called levels of caves or subterranean karst levels. They are closely linked with the phases of valley formation via the main drainage and are in fact their correlated feature within the karst. These theoretical deductions are tested and applied in practice, using as example the cave level of the Holloch in central Switzerland.